Role of silicon dangling bonds in the electronic properties of epitaxial graphene on silicon carbide. (18th February 2016) - Ridene, Mohamed; Kha, Calvin S; Flipse, Cees F J
Abstract: In this paper, we study the electronic properties of epitaxial graphene (EG) on silicon carbide by means of ab initio calculations based on the local spin density approximation +  U method taking into account the Coulomb interaction between Si localized electrons. We show that this interaction is not completely suppressed but is screened by carbon layers grown on-top of silicon carbide. This finding leads to a good qualitative understanding of the experimental results reported on EG on silicon carbide. Our results highlight the presence of the Si localized states and might explain the anomalous Hanle curve and the high values of spin relaxation time in EG.